Contribution of female community health volunteers on the utilization of ANC and PNC by mothers in two districts of Nepal: a Qualitative study - Dhungana, Ashmita; Luitel, Aditya Vinaya; Upadhyay-Dhungel, Kshitiz (Janaki Medical College Journal of Medical Science, 2023)
Background and Objectives: A group that has been credited behind the reduction in child and maternal mortality through programs like immunization, integrated management of childhood illnesses, family planning, and preparing pregnant women for delivery are known as Female Community Health Volunteers (FCHV). FCHVs’ roles have gradually expanded beyond family planning programs and especially are focused on maternal and child health services at a large scale. FCHV is often spoken about or spoken for, but there is little evidence of FCHV's own characterization of their practice. so, this study is designed to explores the roles, practices and experiences of FCHVs in the utilisation of Antenatal care (ANC) and Postnatal Care (PNC) services in two contexts; rural and urban Nepal. Materials and Methods: This is a qualitative study carried out in two districts (one urban and the next rural) viz. Kathmandu and Terathum. Questionnaires leading to in-depth interviews were carried out with 28 FCHVs and 15 service users and Key- Informant Interview with the 8 health facility staff and 15 service users who were purposely selected Data were analyzed using thematic analysis. Results: The study found out that the FCHVs have been involved rigorously on screening and counseling pregnant women on nutritious foods, counseling family about the birth preparedness, institutional delivery, ANC and PNC services provided at the health facility in rural Nepal. While in urban Nepal, the referrals on ANC existed only in those places which were outside the ringroad. The PNC services were not that used by the mothers in rural Nepal while the PNC referrals were not made by urban FCHVs as the maternity hospital itself called for a follow-up. The motivating factors for FCHVs were self-identity, social responsibility and social recognition and status that kept them in doing voluntary workers over the years. Conclusion: FCHVs have been contributing a lot of their time and effort to every possible way to make the women of their community survive while being pregnant or after delivery. This study also underlines some of the differences in the real picture of their roles in urban and rural Nepal.